The Component of Variation Skill Apllied by a Teacher in “Freedom Writers” Film - Norliani (ENLIT, 2021)
Teacher as an educator is one of essential factors to support the success of education in the class, so a teacher must have teaching skills. This research was conducted to find and describe the component of variation skill applied by a teacher in “Freedom Writers “Film This research used descriptive qualitative approach. The data was taken from the movie. Component of variation skill theory used was Turney’s theory (1983). The result of data analysis reveal that the teacher in the movie applied all the component of variation skills, they were variation in teacher’s manner, there are six in this variations, voice variation, focusing, pausing, eyes contact, gesturing and movement. variation in media and material instruction, such as, the use of visual, aural and tactile and also the use of interaction variation.